Seeing Bullshit Rhetorically: Human Encounters and Cultural Values - Leonard Shedletsky (Res Rhetorica, 2018)
This essay explores the idea that calling bullshit exemplifies Mercier and Sperber”s social intuitionist theory. It discusses a range of empirical research related to bullshit, including belief in the worldviews of Individualist vs. Communitarian and Hierarchical vs. Egalitarian with regard to accepting and rejecting ideas. Calling bullshit fits well with using the heuristics of like/not like and cognitive mechanisms of debunking misinformation.